An Analysis on Chinese Idioms Containing the Word “罗” - Stephen Aji Wardana; Rosita Nugraheni; Iffa Mar’atus Shohibul Birri (Universitas Negeri Surabaya, 2025)
Chinese idioms (成语) are an essential part of cultural heritage that reflect meaning, values, and unique expressions of Chinese society. Thus, in order to understand deeper about the meaning and connotations contained in the Chinese Idioms, the writers researched Chinese Idioms specifically contained the word 罗. This study focuses on idioms containing the Chinese character “罗 (luó)”, which etymologically means “net” or “mesh”. Using a semantic framework and descriptive qualitative method, this research analyzes 49 idioms sourced from standard idiom dictionaries, classical literature, and historical texts. The idioms were examined through their denotative and connotative meanings, emotional valence (positive, negative, neutral), and source origins. The findings reveal that idioms with “罗” convey diverse themes, such as entrapment, wealth, distribution, economic hardship, methodology, cultural elements, and foreign-derived terms. Of the total, 27 idioms had positive connotations, 16 were negative, and 6 neutral. The idioms originate from folklore, literary works, historical records, and foreign influences. This study highlights the semantic richness of Chinese idioms and the cultural depth embedded in the character “罗”.